WM1-4 Decompressive craniectomy versus strokectomy for malignant middle cerebral artery (MCA) infarction. Issue 3 (14th February 2019) - Moughal, S; Boeris, D; Hainsworth, A; Pereira, E; Shtaya, A; Minhas, P
Abstract : Objectives: To compare the outcomes of decompressive craniectomy (DC) with craniotomy and debulikng of stroke tissue (Strokectomy (SC)) for malignant MCA infarction at our centre. Design: Retrospective records review. Subjects: All Patients with malignant MCA infraction that underwent DC and SC between Jan 2012 and Sep 2017. Methods: 20 patients had DC (11F/9M, mean age 44.7±1.8 y) and four patients had SC (1F/3M) 51.5±5.9 7 y). Outcomes were assessed by Modified Rankin Scale (mRS) scores before surgery and at latest follow up (3–6 months). mRS was dichotomised as good (0–3) and poor (4–6). Craniotomy size was measured by antero-posterior (AP) diameter and compared between the groups. Results: 18 patients (90%) of the DC group had mRS 4–6 before surgery versus 100% in the SC group. Post-surgery 15 patients (75%) of the DC group had poor outcome with 7 mortalities (35%) in comparison to one patient (25%) with poor outcome in the SC group and no mortalities. The average craniotomy size in DC was 120.1±4.1 mm versus 85.5±13.1 mm in the SC, p=0.003 students t test). Six patients of the DC group underwent cranioplasty where two developed post-operative seizures. There was no significant difference in age, sex and side of craniotomy (7 Left/13 Right in DC vs 2 Left/2 Right in SC). Conclusions: Strokectomy is comparable to decompressive craniectomy in outcomes without taking the extra risks and costs of cranioplasty. Further studies are required to promote this approach.